Improving reading comprehension through Reciprocal Teaching Method - Endang Komariah; Putri Ace Riaula Ramadhona; Tengku Maya Silviyanti (Universitas Syiah Kuala, 2015)
This study is aimed at discovering the benefits of the Reciprocal Teaching Method (RTM) in the reading classroom, finding out the achievements of students after four comprehension training sessions of using RTM, and exploring the perceptions of students on the use of RTM. This method uses four comprehension strategies: predicting, questioning, clarifying, and summarizing, to help learners monitor their development of reading comprehension by themselves. Students work in groups of four or five and the members are divided into five roles which are the leader, predictor, clarifier, questioner, and summarizer. The subjects were 24 students from the twelfth grade at a high school in Banda Aceh. Observations, tests, documents and interviews were collected to get the data. The results showed that the students were more active and productive in the reading classroom after RTM sessions and their reading proficiency improved. They learnt how to apply several of the strategies from RTM while reading. The results also showed that they preferred this method for teaching-learning reading compared to the conventional one. Therefore, teachers are suggested to consider using this method for teaching reading that instils the students on how to apply the four comprehension strategies used in reading.